Zachowania seksualne dzieci i młodzieży ze spektrum autyzmu. Wyniki badań pilotażowych - Wojciechowska, Aneta; Gulczyńska, Anna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
In the article the results of pilot studies concerning manifestation of sexuality in a group of children and youth with autism spectrum disorder were presented. The research is divided into two fundamental parts. In the first part – the shorter one, definitions and conceptions were outlined. The subject of sexuality and functioning of people with autism spectrum disorders regarding social behaviours was also discussed. In the second part, the findings of own studies conducted on a group of mothers of children and youth with autism spectrum disorder were presented.